What is the role of lipids in prion conversion and disease? - Alves Conceição, Cyntia; Assis de Lemos, Gabriela; Barros, Caroline Augusto; Vieira, Tuane C. R. G. (Frontiers in Molecular Neuroscience, 2023)
The molecular cause of transmissible spongiform encephalopathies (TSEs) involves the conversion of the cellular prion protein (PrPC) into its pathogenic form, called prion scrapie (PrPSc), which is prone to the formation of amorphous and amyloid aggregates found in TSE patients. Although the mechanisms of conversion of PrPC into PrPSc are not entirely understood, two key points are currently accepted: (i) PrPSc acts as a seed for the recruitment of native PrPC, inducing the latter’s conversion to PrPSc; (ii) other biomolecules, such as DNA, RNA, or lipids, can act as cofactors, mediating the conversion from PrPC to PrPSc. Interestingly, PrPC is anchored by a glycosylphosphatidylinositol molecule in the outer cell membrane. Therefore, interactions with lipid membranes or alterations in the membranes themselves have been widely investigated as possible factors for conversion. Alone or in combination with RNA molecules, lipids can induce the formation of PrP in vitro-produced aggregates capable of infecting animal models. Here, we discuss the role of lipids in prion conversion and infectivity, highlighting the structural and cytotoxic aspects of lipid-prion interactions. Strikingly, disorders like Alzheimer’s and Parkinson’s disease also seem to be caused by changes in protein structure and share pathogenic mechanisms with TSEs. Thus, we posit that comprehending the process of PrP conversion is relevant to understanding critical events involved in a variety of neurodegenerative disorders and will contribute to developing future therapeutic strategies for these devastating conditions.